2021
DOI: 10.31235/osf.io/atg8p
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Strategic Interdependence and Preferences for Debt Mutualization in the Eurozone

Abstract: Existing research suggests that a “democratic constraint” blocks progress towards debt mutualization in the eurozone: voters in creditor countries fiercely oppose debt sharing, while voters in debtor countries strongly support remaining in the euro, which limits their governments’ bargaining power. However, this literature neglects that preferences depend on expectations about what other countries will do. We document this strategic interdependence with a novel survey experiment in Germany and Italy, conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…However, the fact that a majority of the German population was in favour of the EU recovery fund (Hassenkamp 2020) suggests that public sentiment in Germany is far less entrenched than often assumed (cf. Baccaro et al 2020).…”
Section: The Puzzle Of Germany's Position-taking Towards Emu Reformmentioning
confidence: 99%
“…However, the fact that a majority of the German population was in favour of the EU recovery fund (Hassenkamp 2020) suggests that public sentiment in Germany is far less entrenched than often assumed (cf. Baccaro et al 2020).…”
Section: The Puzzle Of Germany's Position-taking Towards Emu Reformmentioning
confidence: 99%
“…We assume that voters take their cues from such public communications (Chong and Druckman, 2007). The effect of framing on attitudes of voters has been shown for government expenditure (Jacoby, 2000), trade preferences (Ardanaz et al, 2013), redistribution (Harrel et al, 2016), attitudes towards austerity (Barnes and Hicks, 2018), macroeconomic imbalances (Ferrara et al, 2021) and support for the euro (Baccaro et al, 2021). Our analysis takes such framing effects therefore as well-established and goes a step further: whether, and if so which, features of a crisis that policymakers portray in public affect solidaristic attitudes of those who listen.…”
Section: Crisis Frames and Collective Actionmentioning
confidence: 99%
“…Our study is part of recent research efforts to identify the sources of public support for risk sharing in the EU (e.g., Baccaro et al, 2021; Bechtel et al, 2014; Daniele and Geys, 2015; Vasilopoulou and Talving, 2020). Research has also found that, in times of crisis, citizens’ support for European fiscal integration is conditional on the specifics of risk-sharing instruments (Beetsma et al, 2022; Bremer et al, 2021; Vandenbroucke et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This raises the question of the extent to which political elites shape voters’ preferences over European solidarity through the process of information provision and persuasion or the reverse. Recent evidence by Baccaro et al (2020, 2021) for example suggests considerable effects on information provision on public opinion towards the Euro or debt mutualisation within the EU.…”
Section: Review Of the Special Issue Articlesmentioning
confidence: 99%